N and P limitation of fynbos plants and the nutritional status of legume habitats in the Cape Floristic Region - Potgieter, Gardia Purchase (Department of Biological Sciences, 2014)
In general, terrestrial ecosystems are limited by both N and P, but, as legumes fix atmospheric nitrogen, I hypothesized that fynbos legumes would be P limited and nonlegumes would be N limited, and that the degree to which these plants respond to N and P would depend on the levels of each of these two nutrients in the growth media. To test these hypotheses, three legumes and three non-legumes native to the fynbos were grown in a complete factorial arrangement of four levels of N and P in a glass house. Nitrogen was supplied at 20, 40, 80 and 150 mg kg-¹ soil and P at 0.8, 5, 15, and 31 mg kg-¹. Overall, the results showed that the responses of the legume and nonlegume species to N and P supply were species specific, but that the legume species seemed to be more limited by N supply than the non-legumes. There was no N x P interaction in this study, which implied that the plant response to N and P, did not depend on the levels of each other. Given the nitrogen fixing capabilities of legumes and high nutrient demanding lifestyle, I made the hypothesis that, on a given landscape, the soils on which the fynbos legumes occur were more nutrient rich than the bulk non-legume soils. Related to this hypothesis is the question of whether the more nutrient rich soils within the legume populations would be mirrored by leaves with both a higher specific leaf area and higher nutrient concentration, than the leaves of the non-legumes. To test these hypotheses, I determined the nutrient levels of both the soils and plants within both the legume- and non-legumes stands at eight different sites in the CFR. The data were subjected to multifactorial discriminant function analysis and Nested ANOVA analyses. The results of the analyses led to the conclusion that the soil on which legume stands occurred were rarely more fertile than the non-legumes on the landscape in the CFR, and, except for leaf N, there seemed to be no differences between leaf nutrient concentrations and the SLA of the legume and non-legume plants.